Are personal accessories safe in hospital settings? - Maharjan, U; Rajbanshi, L; Gurung, G; Gautam, R; Nepal, HP (Journal of Chitwan Medical College, 2014)
The main goal of this study was to find out whether personal accessories of Health Care Workers (HCWs) harbored microbes which would inhibit good hand hygiene, and would act as breeding grounds for various disease causing microorganisms. Twenty six culture swabs were taken from the bangles, watches and rings of HCWs. We observed the growth of micrococcus species and coagulase negative staphylococci in 50 % of the samples. Of the positive bacterial growth, 45.5% were in bangles, 60% in watches and 40% in rings. Health Care workers have solemn responsibility to safeguard their patients as well as themselves by complying with good hand hygiene compliance by not wearing these accessories during direct patient contact and washing their hands according to WHO Hand Hygiene guidelines. DOI: http://dx.doi.org/10.3126/jcmc.v4i2.10858 Journal of Chitwan Medical College 2014; 4(2): 29-31